Genetic Variants Associated with Early Onset Myocardial Infarction also Associated with Need for Future Revascularization - Vinall, Maria (MD Conference Express, 2009)
A genetic variant that is associated with early-onset myocardial infarction (MI) is also associated with the progression of coronary atherosclerosis and the need for revascularization years after an MI, according to the Italian Genetic Study in Early-Onset Myocardial Infarction.